Case Report: A neonatal case of severe congenital Mycoplasma pneumoniae pneumonia with atelectasis and macrolide resistance - Wang, Dan; Yang, Chunyan; Qin, Daogang; Wang, Jingcai; Zhao, Jing (Frontiers in Pediatrics, 2025)
Reports on congenital Mycoplasma pneumoniae (MP) pneumonia are rare in the medical literature. In this study, we presented a male neonatal case of severe congenital MP pneumonia complicated with atelectasis and macrolide resistance. Empirical treatment with conventional antibiotics proved ineffective and the ventilator could not be weaned. After undergoing five rounds of tracheal intubation, the neonate was successfully weaned off ventilator support after treatment with fluoroquinolone antibiotics combined with bronchoscopic lavage. The diagnoses were based on the early onset of respiratory distress, atypical pneumonia findings on pulmonary imaging, characteristic mucous plugs associated with MP observed during bronchoscopy, and positive MP nucleic acid and IgG antibodies in both the neonate and the mother. Importantly, this case report provides clinical evidence for the treatment of congenital MP infection with atelectasis and macrolide resistance by administering fluoroquinolones at appropriate dosages and durations, along with bronchoscopic lavage as an effective option to clear airway obstruction and improve pulmonary ventilation.